Analisis asesmen diagnostik kognitif materi geometri di kelas IV sekolah dasar - Nisrina Noor Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2024)
The study aims to describe the stages in the cognitive diagnostic assessment of geometry material in grade IV of elementary school which consists of the preparation, implementation and follow up stages. Through a cognitive diagnostic assessment, the teacher can identify the level of student learning readiness regarding geometry material. The research method used is descriptive analysis with a qualitative approach. Data collection techniques obtained through observation, interviews, and documentation. The research was conducted in 2 schools, namely at one of the SDN in Cihideung district and one of the SDN in Tawang district. Based on the research conducted, the results obtained regarding the cognitive diagnostic assessment of geometry material in grade IV of elementary school are as follows: (1) the preparation stage, the class teacher makes a grid of questions and teaching modules as a guide in making questions, (2) the implementation stage, the class teacher delivering geometry material before the test begins, (3) follow up stage, the class teacher provides follow up in the form of remedial and additional lessons. Thus the class teacher can find out the learning needs of students based on cognitive diagnostic assessment of geometry material.